„Mit bardziej współczesny”. O dyskursie wokół polskiego malarstwa przedstawieniowego lat dziewięćdziesiątych - Filip Pręgowski (Miejsce)
The article focuses on the main issues of the discourse on Polish figurative painting of the 1990s. The question is if there were any fundamental changes in the content and form of figurative painting in the times of political and social transformation in Poland. How did the art criticism of the 1990s evaluate figurative painting: its subjects and ways of depicting them? How the previous decade influenced these perspectives?